Path Loss Modeling of Wireless Signals in Underground Tunnels - Yaning Li; Baoguo Yu; Lu Huang (IEEE Open Journal of Antennas and Propagation)
The environmental characteristics of underground tunnels are very different from those of open spaces. Typical features of underground tunnels (sidewall roughness, metal conductors, tunnel inclinations, etc.) significantly affect signal propagation, making it difficult for a single modeling approach to accurately describe the field strength attenuation of a wireless channel in an underground tunnel. In this paper, a hybrid model describing the propagation attenuation of wireless signals in underground tunnels is proposed, which divides the propagation channel into three subdomains according to the length of the tunnel, namely, the region of the free space propagation model, the region of the multimode propagation described by the ray tracing method, and the region of the improved waveguide model by adding the influences of tunnel roughness, tunnel inclination, and metal pipes. The determination of the breakpoints separating each region depends on the variation of the angle between the arrival direction of the signal ray and the axial direction of the tunnel. The proposed channel model is validated by simulation and experimental measurements, and the results show that the proposed model agrees well with the measured data and outperforms the current most advanced channel propagation fading model, with a 16.2% reduction of model error for the empty straight tunnel, and a 32.0% reduction of model error for the tunnel with metal pipes.